Mapping Publication Trend of E-Government Development Index (Social Science Discipline Analysis) - Sukarno, Mohamad; Mutiarin, Dyah (SCAD Independent, 2024)
This study aims to determine the research development with the Theme E-Government Development Index (EGDI) from 2003-2023. The method used in this study is qualitative with literature study. This research data source uses the Scopus database to identify research themes related to the EGDI for the 2003-2023 period, with a total of 240 article documents indexed by Scopus. Data analysis in the study used VOSviewer and NVivo 12plus to analyze the data and classify the research theme. The results showed that 2011 became the highest year in published Scopus-indexed articles. China is the country that has the highest contribution to research publications. Aii, Janowksi, Khawula, Khan, and Marthins were the main contributors to contributing publications. Then, the topics of electronic commerce, government data processing, government, e-government, and electronic health food became the highest frequency score for occurrences. The system is the most crucial topic in every research publication under the Theme of EGDI indexed by Scopus from 2003-2023. This research contributes theoretically to measuring e-government development in a country and practical in public service ICT innovation.